2022
DOI: 10.1039/d1nr08235c
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on photocatalytic reduction of CO2 based on LDH materials

Abstract: Converting CO2 to renewable fuels or valuable carbon compounds is an effective way to solve the global warming and energy crisis. Compared with other CO2 conversion methods, photocatalytic reduction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 166 publications
0
43
0
Order By: Relevance
“…LDHs as encouraging photocatalysts came out to be vigorously studied as a result of the lamellar structure and extraordinary semiconducting and adsorption properties. LDHs with tunable composition, large surface area, and high quantity of available surface-active sites have received huge interest for photocatalytic CO 2 reduction . Although LDH as a layered semiconductor has the ability to enhance the photocatalytic performance, it endures from weak charge mobility and quick charge recombination, resulting in a low photocatalytic activity toward CO 2 reduction. , To overcome these problems, the formation of LDH/TiC MXene could proficiently amalgamate multifunctionalities, recompense deficiencies, and bestow new properties, which make efficient charge carrier separation, resulting in stability and higher photocatalytic performance.…”
Section: Ldh-based Tic Mxene Composites For Energy Storage and Conver...mentioning
confidence: 99%
See 2 more Smart Citations
“…LDHs as encouraging photocatalysts came out to be vigorously studied as a result of the lamellar structure and extraordinary semiconducting and adsorption properties. LDHs with tunable composition, large surface area, and high quantity of available surface-active sites have received huge interest for photocatalytic CO 2 reduction . Although LDH as a layered semiconductor has the ability to enhance the photocatalytic performance, it endures from weak charge mobility and quick charge recombination, resulting in a low photocatalytic activity toward CO 2 reduction. , To overcome these problems, the formation of LDH/TiC MXene could proficiently amalgamate multifunctionalities, recompense deficiencies, and bestow new properties, which make efficient charge carrier separation, resulting in stability and higher photocatalytic performance.…”
Section: Ldh-based Tic Mxene Composites For Energy Storage and Conver...mentioning
confidence: 99%
“…Under light irradiations, the photoinduced generated electrons and holes can transfer from the CB or VB of the semiconductor, respectively, to the co-catalyst, constraining the recombination of the charge carrier. Also, the active sites available for the reduction and oxidation half reactions are split, and consequently, the photocatalytic conversion efficiency can be improved substantially . The improvement in properties of the LDH through coupling with TiC MXene is given in Figure .…”
Section: Ldh-based Tic Mxene Composites For Energy Storage and Conver...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the developed photocatalysts, transition metal hydroxides, as noble‐metal‐free cocatalysts, are attractive because they are naturally abundant, cost effective, and have high CO 2 adsorption capacity. [ 9–11 ] In particular, Ni(OH) 2 has been demonstrated to be a superior cocatalyst for CO 2 reduction. For example, Peng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, CH 3 OH, HCOOH, CH 4 and CO are the major reduced products arising from the photoreduction of CO 2 . 153 CO 2 reduction into CO and H 2 is a requisite task to produce syngas for upgradation of fuel via Fischer–Tropsch synthesis. In the wake of this necessity, Wang et al 46 reported Pd nanoparticle loaded CoAl-LDH (Pd/CoAl-LDH) in conjunction with ruthenium complex (a photosensitizer; [Ru(bpy) 3 ]Cl 2 ·6H 2 O) as a heterostructure photocatalyst for CO 2 reduction to syngas under visible light irradiation.…”
Section: Photocatalysts For Syngas Productionmentioning
confidence: 99%